Photoluminescence and photocatalytic degradation studies on some metallophthalocyanines - Pavaskar, Puzy; Chodankar, Sangeeta; Salker, Arun (European Journal of Chemistry, 2011)
This paper deals with the up-conversion intrinsic photoluminescence by exciting the Metallo-Phthalocyanine (MPc) prepared by melt method. MPcs were further characterized using UV visible spectrophotometer, FT-IR, and thermal analysis. The magnetic susceptibility, optical absorption and photoluminescence behavior of these compounds were studied. Photocatalytic degradation of amido black 10B dye using different MPcs at varing pH was done to see the efficiency of these compounds. High emission intensity and easy preparation makes these systems potential candidates for application as luminescent material.